PERILAKU KECANDUAN MEROKOK DAN KEPERCAYAAN DIRI SISWA SMA TRI BHAKTI PEKANBARU - Susilawati, Susilawati; Rosmawati, Rosmawati; Yakub, Elni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The development of the Era of Globalization in the 21st century has caused many remarkable changes. These changes also arise problems that can cause destruction and damage in many ways, not apart also in the world of education. Bringing great impact with the occurrence of behavior deviation among students, one of which is smoking addiction behavior. The high level of cigarette consumption for teenagers as well as the young age of starting to smoke among students need to get special attention again. Objectives of the study 1) To know the description of smoking addiction behavior of high school students Tri Bhakti Pekanbaru. 2) To know the confidence of students addicted to smoking in SMA Tri Bhakti Pekanbaru. The research method is descriptive quantitative, with purposive sampling technique. Research conclusions 1) The level of smoking addiction behavior in students is in the high category. While the behavior of smoking with the number of cigarettes in the suction per day between 10-20 stems per day; the amount of cigarettes per day between Rp 10.000-20.000; age started smoking at age 9 years; the source of the cigarette money comes from work; daily smoking time which starts with 5 minutes after waking up; the reason to start smoking is because they have friends who smoke and smoke together; and where smoking is marked by smoking in public places with friends in familiar places of association. 2) The level of confidence in students is in the high category. While confidence shows responsible results; rational; optimistic; belief in self-efficacy; and objective. For confidence in the show include able to complete personal needs; schools make rules to be more disciplined; has advantages that can be developed; doing something will be done to completion even if it is difficult; and are confident of a good future if you want to learn earnestly and success is gained by trying.Key Words : Smoking Addiction Behavior, Self Confidence